FACTORS INFLUENCING MISMANAGEMENT OF DEVOLVED PUBLIC FUNDS AND ITS EFFECTS ON SERVICE DELIVERY IN NAIROBI COUNTY - Nyamweya, Penwel N.; Osuga, Mr. Ben O. (Journal of Public Policy and Administration, 2017)
Purpose: To determine the factors influencing mismanagement of devolved public funds and its effects on service delivery in Nairobi County. Methodology: The study utilized a descriptive research design. Findings: Results revealed that policy framework and proper internal control system have a significant relationship with service delivery. This implies that good policy framework and proper internal control system in Nairobi County can result to better/improved service delivery within the county. Results also revealed that training of personnel have a significant relationship with service delivery. This implies that training of personnel in Nairobi County can result to better/improved service delivery within the county. Further, results revealed that staff motivation have a significant relationship with service delivery. This implies that staff motivation in Nairobi County can result to better/improved service delivery within the county. Unique contribution to theory, practice and policy: This study will be significant to various groups of people. These include the government and monetary authorities, academicians and researchers and workers. The government and monetary authorities are the major policy makers when it comes to county government decisions. The recommendations of this study will enable them understand the condition with which employees perform better and avoids mismanagement of public funds. Empirical studies on mismanagement of public funds and service delivery in Kenya are particularly scarce. This study will hopefully stimulate further research in the area which has been a grey area for some time. The study will help workers and their representatives to know the causes for mismanagement of their funds. This will in turn pave way for them (workers) to advise accordingly.